Sequential Estimation of the Radial Temperature Variation in Overhead Power Cables. Issue 18 (26th July 2022) - Absi Salas, Farith M.; Orlande, Helcio R. B.; Domingues, Luis A. M. C.; Barbosa, Carlos R. N.
Abstract: Cables used in electric power transmission lines are usually composed of layers of stranded metallic wires. Several effects cause a nonuniform distribution of the electric current, which significantly influences heat generation within the cable. The accurate prediction of the cable radial temperature variation is thus of great importance for the design and operation of electric power transmission lines, because of economic and safety reasons. In this work, the Particle Filter method is applied to estimate the transient temperature distribution in the cross section of an Aluminum Conductor Steel Reinforced power cable, by using measurements of the cable surface temperature obtained with an infrared camera. The Sampling Importance Resampling (SIR) algorithm of the Particle Filter method is used for the solution of the state estimation problem, by taking into account uncertainties in the evolution heat conduction model within the cable, as well as in the measured temperatures. The results presented in this work reveal an excellent agreement of the estimated temperatures obtained with the SIR algorithm and temperature measurements from thermocouples inserted into the cable during the manufacturing process, thus validating the proposed approach for the estimation of the radial temperature variation in the power cable.